PENERIMAAN E-LEARNING DENGAN TECHNOLOGY ACCEPTANCE MODEL PADA UIN SUNAN AMPEL SURABAYA - Merlin Apriliyanti; Ilham (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The existence of information technology and information systems has changed many organizations around the world. Information technology promises significant potential for organizations to improve operational capabilities. The benefits that e-learning brings are more flexible learning opportunities, saving space and time, facilitating access to education for the community, enriching learning materials, and facilitating the learning process. This study aims to evaluate, to convince, to know the extent of the influence of model technology acceptance on the use of E-Learning. The population in this study is the State Islamic Religious University UIN Sunan Ampel Surabaya, which is located in the city of Surabaya. the minimum number of samples in this study was 170 lecturers and students. The sampling technique in this research is sampling based on the research population using the Proportional Random Sampling technique. Researchers use structural equation modeling in analytical techniques, considering that SEM has the ability to combine measurement models with structural models simultaneously and efficiently. The results of the statistical analysis of the application of the TAM and UTAUT models using the AMOS software found several factors including Social Influence, Facilitating Condition, Perceived Usefulness, and Perceived Ease of Use directly affect Use Behavior and empirically proven to affect the behavior of lecturers and students in using e-learning for online learning activities at UIN Sunan Ampel Surabaya.